2017
DOI: 10.1016/j.bbadis.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet leads to O-GlcNAc modification in the BTBRT+tf/j mouse model of autism

Abstract: The KD has tissue specific impacts on O-GlcNAc. Although levels of O-GlcNAc play an important role in neurodevelopment, levels of this modification in the juvenile mouse brain were stable with the KD despite large fluctuations in energy status. This suggests that it is unlikely that the KD exerts it therapeutic benefit in the BTBR model of ASD by O-GlcNAc related pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…The researchers of animal model studies proved that KD might be an effective intervention in alleviating ASD symptoms [52,53]. Furthermore, larger cohort studies found that the use of KD results in noticeable improvements in: learning, social behaviour, speech, cooperation and reduction of hyperactivity in ASD patients [5,40,54].…”
Section: Dietary Models In Asdmentioning
confidence: 99%
“…The researchers of animal model studies proved that KD might be an effective intervention in alleviating ASD symptoms [52,53]. Furthermore, larger cohort studies found that the use of KD results in noticeable improvements in: learning, social behaviour, speech, cooperation and reduction of hyperactivity in ASD patients [5,40,54].…”
Section: Dietary Models In Asdmentioning
confidence: 99%
“…The studies comprised 103 rat studies, 63 mouse studies, 2 that included rats and mice, and 1 that included rats and gerbils as well as a canine case study. There was a range of nervous system dysfunction models, including five age-related degeneration (42)(43)(44)(45)(46) , four Alzheimer's disease (47)(48)(49)(50) , seven autism (51)(52)(53)(54)(55)(56)(57) , four cerebral ischaemia (58)(59)(60)(61) , two pain perception (16,62) , twenty-four general central nervous system , two diabetes (87,88) , ninety-one epilepsy , two metabolic syndrome (180,181) , one mild cognitive impairment (182) , two multiple sclerosis (183,184) , one nerve toxin (185) , four optic nerve dysfunction (186)(187)(188)(189) , two Parkinson's disease (190,191) , three peripheral nerve dysfunction (192)(193)(194) , four spinal cord injury (195)(196)(197)(198) , three stroke (199)…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…There is much evidence showing that insulin, another metabolic hormone, phosphorylates and activates OGT through the insulin receptor (Whelan et al 2008 ). Feeding animals a ketogenic diet, which may affect HBP flux, altered OGT and OGA gene expression without affecting total O-GlcNAc content in the prefrontal cortex (Newell et al 2017 ). Hence, in the hippocampus, there is clear evidence that neuronal O-GlcNAc levels are nutrient-dependent.…”
Section: O-glcnac and Its Regulation In The Nervous Systemmentioning
confidence: 99%